Exercise and Weight Management: The Role of Leptin—A Systematic Review and Update of Clinical Data from 2000–2022 - de Assis, Gilmara Gomes [UNESP]; Murawska-Ciałowicz, Eugenia (MDPI, 2023)
A well-balanced metabolism means a lower risk for metabolism-related neuropsychiatric disorders. Leptin is a secretory adipokine involved in the central control of appetite that appears to play a role in the etiology of feeding-related disorders. Additionally, the influence of exercise on feeding behaviors potentially modulates the circulation of metabolites that signal through the central nervous system. In this systematic review, we collected the recent clinical evidence on the effect of exercise on leptin concentrations in health individuals published from 2000 to 20 September 2022, according to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA 2020 statement). Six hundred and thirty-eight papers were retrieved and forty-eight papers were included in the qualitative synthesis. Data supports that exercise positively influences appetite via enhancing peripheral and central leptin signaling (reuptake), especially during weight loss. Exercise modulation of leptin signaling through leptin receptors helps to stabilize increases in food intake during periods of negative energy balance, prior to a decrease in the body fat tissue content. At a high intensity, exercise appears to counteract leptin resistance.
Keywords: appetite; feeding disorders; leptin; metabolism; weight loss